Clinical Scenario of Pseudomyopia Before and After Vision Therapy: Two Case Reports - Chhetri, Santosh; Magar, Suraj Thapa; Adhikari, Srijana; Belbase, Umesh (Nepalese Journal of Ophthalmology, 2024)
Introduction: Cycloplegic agents are the most common method used for accommodation relaxation in accommodative spasm cases. However, concerns have arisen about the possibility of rebound effects following the cessation of cycloplegic treatment. This case reports demonstrates a clinical approach for managing accommodative spasm, utilizing the modified Borish’s delayed subjective technique and vision therapy. Additionally, also evaluates the patient’s clinical status after six months of cessation of therapy. Case Report 1: A 9-year-old female presented with a headache and blurred vision. Her presenting visual acuity was 1/60 in each eye and variable myopia reached up to -6.00 diopters spherical. Cycloplegic refraction showed a low hyperopia and improvement in visual acuity to 6/9 in each eye. This confirmed the diagnosis as accommodative spasm and was referred to a vision therapy clinic for further management. Case Report 2: A 13-year-old female presented with 6/36 visual acuity in both eyes and variable myopic refractive error but cycloplegic refraction revealed low hyperopia and improvement in visual acuity. Then, she was referred to optometry and vision therapy clinic. Conclusion: A modified Borish’s delay subjective technique can be applied to instantaneous relief of accommodative spasm. Vision therapy can be useful in restoring normal accommodative and vergence functions. Sustained improvement in visual function and stability of accommodation is obtained after six months of cessation of vision therapy.